通气式音频换能器 (2024)
本公开涉及通气式音频换能器。本主题技术的具体实施提供诸如通气式扬声器的通气式音频换能器。扬声器组件能够限定所述扬声器的圆顶下的第一容积和所述扬声器的环绕件下的第二容积。所述第一容积和所述第二容积能够由诸如音圈的扬声器结构分开。通过将第一容积向第二体积通气，所公开的通气式扬声器能够通过在操作期间均衡所述振动膜下的压力，在高频下提供比常规扬声器更平坦的响应和更低的失真。 Implementations of the subject technology provide vented audio transducers such as vented speakers. A speaker assembly may define a first volume under a dome of the speaker and a second volume under a surround of the speaker. The first volume and the second volume may be separated by a speaker structure such as a voice coil. By venting the first volume to the second volume, the disclosed vented speakers can provide a flatter response at high frequencies and lower distortion relative to conventional speakers, by equalizing the pressure under the diaphragm during operation.